Adrenocortical Carcinoma with Infiltrated and Ruptured Inferior Vena Cava in Adult Woman - Maligan, Deden Jinar Wahyudi; Maulana, Akhada; Danurdoro, Aria; Santosa, Hilda; Kumaladewi, Baiq Ratna (http://dharmais.co.id/, 2025)
Introduction: Adrenocortical carcinoma (ACC) is a malignant tumor that develops in the adrenal cortex. This case involves a rare, aggressive disease that demands specialized knowledge and optimal treatment for a favorable prognosis. This study aims to present the case of a woman with a right-sided ACC extending into the inferior vena cava (IVC), managed through radical resection and IVC repair.Case Presentation: A 50-year-old female presented with a complaint of a lump in the upper right abdomen, which she noticed three months ago. Abdominal computed tomography (CT) scan with contrast revealed a solid, inhomogeneous mass in the right suprarenal region measuring 12 cm x 11 cm. However, three days before the scheduled operation, the patient was brought to the emergency department with complaints of weakness and muscle weakness throughout the body. During the surgery, an adrenalectomy on the right side revealed a tumor infiltrating the IVC, causing venous rupture. The histological examination of the right adrenal tissue revealed ACC, infiltration of tumor cells beyond the capsule, lymphovascular infiltration, and no evidence of tumor cell infiltration into the kidney tissue. The treatment approach for this ACC case involved a complete surgical resection with open adrenalectomy and vena reconstruction. Postoperative results indicated improved patient condition, including symptom relief and favorable biochemical evaluation after surgery.Conclusion: Our patient had a right-sided ACC with local vascular infiltration into the IVC.